Development of low-cost robotic hands for introduction to mechatronics engineering courses - Ali, Muhammad Aminuddin Anwar; Zainul Azlan, Norsinnira; Mohd Safian, Kamil Alif (Asian Research Publishing Network (ARPN), 2016)
Mechatronics engineering is a broad discipline involving the integration of mechanical engineering, electrical engineering, telecommunications engineering, control engineering and computer engineering. It is well-known that laboratory or hands-on works enhance the learning process in this class. This study proposes the development of low-cost anthropomorphic robotic hands, namely the Spring Hand and EMG Hand for the introduction to mechatronics engineering courses. The robots have a close physical appearance as human hand and the utilization of the robotic hands in learning basic mechatronics concepts will make the studying process more fun and spark the students’ interest. The developed robotic hands are low-cost and incorporated with infrared, force and muscle sensor, Arduino UNO board and servomotors. Experiments results from the proposed robotic hand are presented in this paper.